Design A Mini Power Bank As A Storage Electrical Energy of Dragon Fruit Stems - Eza Rahmadani Rahmadani; Helendra Helendra; Husna Husna (Universitas Islam Negeri (UIN) Mataram, 2022)
Research has been done on designing a mini power bank using dragon paste as a source of electrical energy. The voltage and current generated by this dragon paste and power bank are measured using a digital multimeter. Dragon paste is used in series and parallel. The voltage generated by the dragon paste is connected to a DC step up. The use of step-up dc aims to increase the dragon paste voltage so that it can or can charge lithium-ion batteries that have been arranged in parallel using the power bank kit module. Keywords: Dragon Paste, Module Kit, Powerbank